Glutamine synthetase inactivation by protein–protein interaction - García-Domínguez, Mario (The National Academy of Sciences, 1999)
Glutamine synthetase (GS; EC 6.3.1.2) is the pivotal enzyme of nitrogen metabolism in prokaryotes. Control of bacterial GS activity by reversible adenylylation has provided one of the classical paradigms of signal transduction by cyclic cascades. By contrast, in the present work we show that cyanobacterial GS is controlled by a different mechanism that involves the interaction of two inhibitory polypeptides with the enzyme. Both inactivating factors (IFs), named IF7 and IF17, are required in vivo for complete GS inactivation. Inactive GS-IF7 and GS-IF17 complexes were reconstituted in vitro by using Escherichia coli-expressed purified proteins. Our data suggest that control of GS activity is exerted by regulating the levels of IF7 and IF17.